Visual camouflage. Issue 3 (3rd July 2018) - Pettersson, Rune
Abstract: There are many examples of visual camouflage among animals, and in the military. The objective with camouflage by crypsis is to become invisible by blending in with the background or by disruption of outlines. The objective with camouflage by mimesis is to become totally ignored and unnoticed. The objective with camouflage by dazzle is to confuse the opponents. Some visual camouflage may be called cultural camouflage . Here people use disruptive pattern materials to express ideas. We may see visual deceptive camouflage as a special kind of information design.